2014
DOI: 10.4103/0377-4929.134729
|View full text |Cite
|
Sign up to set email alerts
|

Endometrioid carcinoma infiltrating atypical leiomyoma: A mimicker of malignant mixed Mullerian tumor

Abstract: Atypical or symplastic leiomyoma is a rare histological variant of leiomyoma. This is a case report of 63-year-old patient who underwent hysterectomy with bilateral salpingo-oophorectomy. Histopathology of the polypoid growth seen in the endometrial cavity revealed atypical leiomyoma infiltrated by endometrioid cancer. Atypical leiomyoma can be misdiagnosed as leiomyosarcoma. Thus, carcinosarcoma was ruled out as it has an ominous prognosis. A diagnosis of atypical leiomyoma infiltrated by endometrioid cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Kurotaki et al, [ 1 ] reported a case of adenocarcinoma of the endometrium extending into the leiomyoma of the uterus in a rabbit. Qury et al, [ 2 ] reported for Endometrioid carcinoma infiltrating atypical leiomyoma and pointed the necessity of ruling out carcinosarcoma as it has an ominous prognosis. Toshiki et al, [ 3 ] reported a similar case of adenocarcinoma arising in adenomyosis without endometrial involvement, but there were already lymph node metastasis and serous uterine involvement by the time of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kurotaki et al, [ 1 ] reported a case of adenocarcinoma of the endometrium extending into the leiomyoma of the uterus in a rabbit. Qury et al, [ 2 ] reported for Endometrioid carcinoma infiltrating atypical leiomyoma and pointed the necessity of ruling out carcinosarcoma as it has an ominous prognosis. Toshiki et al, [ 3 ] reported a similar case of adenocarcinoma arising in adenomyosis without endometrial involvement, but there were already lymph node metastasis and serous uterine involvement by the time of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%